Mathematical Connections to the Demand and Supply Functions of MSME Products in Pelawi Utara Subdistrict - Nina Fadilah; Ikhah Malikhah; Minarti Sri Wachyuni; Nanda Puspa Rahmadani; Ramandha (The International Conference on Education, Social Sciences and Technology (ICESST), 2024)
This service aims to socialize the mathematical connection to the concept of Element (demand and supply for MSME products in North Pelawi Village, Babalan District, Langkat Regency. This service activity is carried out by a service team consisting of lecturers and students who aim to provide briefings in the form of socialization to the community of business actors and MSME owners where with this activity it is hoped that there will be awareness and motivation of business actors to relieve the importance of applying mathematical concepts in the context of the connection or tension between the amount of demand and supply. So to predict the amount of demand and the amount of supply at a certain price is not difficult. Because with the ability to predict and control the number of goods offered, the price will be able to be conditioned to be stable and still within reasonable limits. For this reason, the role of business actors has a great influence on the sustainability and development of the business carried out so that the goal of obtaining maximum profits for better MSME performance is obtained. This service was carried out in North Pelawi Village by previously recording business actors around North Pelawi Village with the aim that MSMEs that have been run so far can better apply an understanding of mathematical concepts that are connected to the demand and supply elements for products produced in a certain period or period of time.